Mic1-3 Knockout Toxoplasma gondii is a good candidate for a vaccine against T. gondii-induced abortion in sheep - Mévélec, Marie-Noëlle (EDP Sciences, 2010)
This study assessed the effectiveness of a mutant strain of Toxoplasma gondii (RH strain) lacking the mic1 and mic3 genes (Mic1-3KO) against Toxoplasma abortion in sheep. Ewes were inoculated subcutaneously with 10(5) Mic1-3KO tachyzoïtes in three independent experiments. Following vaccination, Mic1-3KO induced a mild febrile response and serum IgG antibodies, which persisted throughout the experiments. Tissue cysts formed in the sheep, but were not, under our experimental conditions, infectious when given orally. Ewes were mated two months after vaccination and were orally challenged with the PRU strain of T. gondii at mid-gestation (400 oocysts in Experiments 1 and 2; 100 oocysts in Experiment 3). Challenge of vaccinated pregnant ewes resulted in a slight febrile response, whereas unvaccinated ewes developed a more severe, characteristic febrile response of longer duration. After challenge, all unvaccinated ewes aborted whereas 62%, 91% and 64% (Experiments 1, 2 and 3 respectively) of the lambs from vaccinated ewes were viable, with no clinical signs of infection. Mic1-3KO was as effective as S48, the strain used as a live vaccine for sheep (Toxovax(®)). A dose of 10(5) Mic1-3KO tachyzoites was sufficient to induce protection (versus a dose of 2 × 10(6)). Both subcutaneous and intraperitoneal injections were effective. Moreover, preliminary results showed the potential of Mic1-3KO to reduce the development of tissue cysts in lambs born to vaccinated ewes. This study demonstrates that Mic1-3KO is a potent vaccine candidate.